2024
DOI: 10.31219/osf.io/nvzuq
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Role of Cognates and Language Distance in Simultaneous Bilingual Children’s Productive Vocabulary Acquisition

Elly Koutamanis,
Gerrit Jan Kootstra,
Ton Dijkstra
et al.

Abstract: This study examined the influence of cognate status and language distance on simultaneous bilingual children’s vocabulary acquisition. It aimed to tease apart effects of word-level similarities and language-level similarities, while also exploring the role of individual-level variation in age, exposure, and non-target language proficiency. Children simultaneously acquiring two closely related languages (n = 203) or two more distant languages (n = 109) performed extended versions of the LITMUS Cross-linguistic … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Still, Dutch and Greek are related (as both are Indo-European languages) and share a certain number of cognates, which may affect the extent to which cognate effects occur. Indeed, Koutamanis et al (2024) found that language distance can influence the strength (but not necessarily the occurrence) of cognate effects. Future studies may further investigate cognate effects in languages which are related to each other to differing degrees.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Still, Dutch and Greek are related (as both are Indo-European languages) and share a certain number of cognates, which may affect the extent to which cognate effects occur. Indeed, Koutamanis et al (2024) found that language distance can influence the strength (but not necessarily the occurrence) of cognate effects. Future studies may further investigate cognate effects in languages which are related to each other to differing degrees.…”
Section: Strengths and Limitationsmentioning
confidence: 99%